Mitigasi Risiko Supply Chain Pada Toko Roti XYZ Menggunakan Metode Analytic Network Process (ANP) - Bernadetha Dara Jingga Asmara; Nabila Noor Qisthani; Mikael Krisnata Robertus Panjaitan (President University, 2023)
The XYZ bakery produces around 2000 bread every day, with large production results, of course, quite a lot of risks in the production process ranging from the availability of raw materials, production failures, to delays in shipping. This can cause losses to The XYZ Bakery, so it is necessary to prevent and control it to reduce the losses arising from the risks that occur. The purpose of this study is to analyze the risk of supply chain using the ANP (Analytic Network Process) method until the risk priority is obtained for further determination of mitigation strategies at the XYZ bakery. The matrix limit results show the highest risk weight is the risk of bread that is not sold, which is 0.193759, so this risk will be a priority risk to be mitigated. Alternative mitigation is obtained by brainstorming at a bakery and sees previous journal research. Based on calculations with the ANP method, the mitigation priority selected to be applied to the XYZ bakery is to sell bread at discount or donated prices.